KORELASI KETERAMPILAN MEMBACA APRESIATIF CERPEN DENGAN KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI MADRASAH ALIYAH NEGERI 1 LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - M. Hafrison, Della Melaty, Irfani Basri, (Universitas Negeri Padang, 2017)
The purpose of this study is. First, describe the skill of reading appreciation of students of class XI Madrasah Aliyah Negeri 1 Linggo Sari Baganti Pesisir Selatan Regency. Second, describe the skill of writing short stories of students of class XI Madrasah Aliyah Negeri 1 Linggo Sari Baganti Pesisir Selatan Regency. Third, analyze the correlation between reading skill appreciative skill with short story writing skill of student of XI Madrasah Aliyah Negeri 1 Linggo Sari Baganti Pesisir Selatan Regency. This type of research is quantitative research with descriptive method. The design of this research is correlational design. Population in this research is student of class XI Madrasah Aliyah Negeri 1 Linggo Sari Baganti Regency of South Pesisir registered in academic year 2016-2017. The sample of this research is determined by using random sampling technique. The variables of this research are the reading appreciative skill of the short story as the independent variable and the skill of writing short story text as the dependent variable. The data of this research is the score of reading skill test for the students of class XI Madrasah Aliyah Negeri 1 Linggo Sari Baganti Pesisir Selatan Regency and the score of skill test result of the students' writing skill in class XI Madrasah Aliyah Negeri 1 Linggo Sari Baganti Pesisir Selatan Regency.Â Kata kunci: membaca, membaca apresiatif cerpen, menulis teks cerpen